Wide-Ranging Analysis of MicroRNA Profiles in Sporadic Amyotrophic Lateral Sclerosis Using Next-Generation Sequencing - De Felice, Bruna; Manfellotto, Francesco; Fiorentino, Giuseppe; Annunziata, Anna; Biffali, Elio; Pannone, Raimondo; Federico, Antonio (Frontiers in Genetics, 2018)
MicroRNA (miRNA) has emerged as an important regulator of gene expression in neurodegenerative disease as amyotrophic lateral sclerosis (ALS). In the nervous system, dysregulation in miRNA-related pathways is subordinated to neuronal damage and cell death, which contributes to the expansion of neurodegenerative disorders, such as ALS. In the present research, we aimed to profile dysregulation of miRNAs in ALS blood and neuromuscular junction as well as healthy blood control by Next Generation Sequencing (NGS). The expression of three up-regulated miRNAs, as miR-338-3p, miR-223-3p and miR-326, in the ALS samples compared to healthy controls, has been validated by qRT-PCR in a cohort of 45 samples collected previously. Bioinformatics tools were used to perform ALS microRNAs target analysis and to predict novel miRNAs secondary structure. The analysis of the NGS data identified 696 and 44 novel miRNAs which were differentially expressed in ALS tissues. In particular, in neuromuscular junction the differential expression of miR-338-3p, which we previously found up-regulated in different types of ASL tissues, miR223-3p, and miR-326 was elevated compared to normal control. ALS microRNAs gene target were significantly involved in neuronal related pathway as BDFN1 and HIF-1genes. Moreover, novel miRNAs were identified showing a significantly differential expression in neuromuscular junction ALS samples. This study presents the direct experimental evidence that, overall, miR-338-3p is highly expressed in ALS tissues including neuromuscular junction characterizing ALS from normal tissues. Beside, our analysis identified, for the first time, novel microRNAs highly expressed in ALS tissues. In conclusion, the results indicate that miRNAs has an important role in the diagnosis and treatment of amyotrophic lateral sclerosis.